2021
DOI: 10.1186/s12885-021-08415-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with emergency-onset diagnosis, time to treatment and type of treatment in colorectal cancer patients in Norway

Abstract: Background International differences in survival among colorectal cancer (CRC) patients may partly be explained by differences in emergency presentations (EP), waiting times and access to treatment. Methods CRC patients registered in 2015–2016 at the Cancer Registry of Norway were linked with the Norwegian Patient Registry and Statistics Norway. Multivariable logistic regressions analysed the odds of an EP and access to surgery, radiotherapy and sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Aside from initial tumor stage, the emergency with which primary tumor is resected could be a factor to explain the lower OS. Published studies demonstrated that elective surgeries were associated with better patient' clinical outcomes than emergency CRC primary tumor resections, even with local complications 36‐38 . Our results showed that the rate of elective primary tumor resections reached around 70% over time and did not decrease after 2020.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Aside from initial tumor stage, the emergency with which primary tumor is resected could be a factor to explain the lower OS. Published studies demonstrated that elective surgeries were associated with better patient' clinical outcomes than emergency CRC primary tumor resections, even with local complications 36‐38 . Our results showed that the rate of elective primary tumor resections reached around 70% over time and did not decrease after 2020.…”
Section: Discussionmentioning
confidence: 55%
“…Published studies demonstrated that elective surgeries were associated with better patient' clinical outcomes than emergency CRC primary tumor resections, even with local complications. [36][37][38] Our results showed that the rate of elective primary tumor resections reached around 70% over time and did not decrease after 2020. A study in Australia and New Zealand and a single-site Japanese study found a significantly larger share of urgent CRC cases during the pandemic.…”
Section: Delays Between Mdms and Tumor Resectionsmentioning
confidence: 65%
“…However, strong associations between emergency presentation and mortality prevail even after adjustment for comorbidity. 15 , 21 , 27 , 28 Rural or urban patient residence might also be associated with differential risk of emergency presentation. 29 Another possible confounder (eg, of associations with age) is screening detection status, particularly in colorectal cancer, although there were no suitable data to enable such an analysis to be done.…”
Section: Discussionmentioning
confidence: 99%
“…Inequality in cancer care, especially expensive treatments, has previously been described in relation to sex, age and SES, including educational level and marital status [ 28 30 ]. Moreover, cancer patients with lower SES have worse survival prospects [ 31 ].…”
Section: Discussionmentioning
confidence: 99%